Activation of bovine factor X (Stuart factor): conversion of factor Xaalpha to factor Xabeta. - Fujikawa, K (1975)
Bovine factor X (molecular weight 55,100) is a blood coagulation factor present in plasma in a precursor or zymogen form. It is a glycoprotein which has been isolated as a two-chain structure held together by one or more disulfide bonds. During the coagulation process, factor X is converted to a serine protease by the hydrolysis of a specific peptide bond in the amino-terminal region of the heavy chain. This cleavage occurs between Arg-51 and Ile-52, giving rise to factor Xaalpha (molecular weight 45,300) and an activation peptide (molecular weight 9500). Factor Xaalpha is then converted to factor Xabeta (molecular weight 42,600) by hydrolysis of a second specific peptide bond in the carboxyl-terminal region of the heavy chain. This cleavage occurs between Arg-290 and Gly-291, giving rise to a second glycopeptide (molecular weight 2700). Factor Xaalpha and factor Xabeta have equivalent coagulant activity, indicating that the cleavage of the second peptide bond is unrelated to the activation process.